2021
DOI: 10.1155/2021/6389001
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual Reality-Based Analysis of Pressure Ulcer Care Information Related to Medical Equipment for the Prevention of Pressure Ulcer Skin Foam Dressings in the Elderly

Abstract: As the standard of life has increased with the advancement of the time, there has been an increasing stress on healthcare with the aging diet, and pressure sores occur in elderly hospitalized subjects. Of course, the emergence of related medical devices, especially auxiliary foam dressings, is constantly improving. Pressure ulcers are extremely harmful to the elderly. The use of virtual reality technology to simulate the treatment of foam excipients is to test the role of medical devices in virtual reality. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…treatments are used more frequently for pressure injuries of various stages. [38][39][40] However, these dressings are considered prophylactic rather than therapeutic. 41 Modern dressings facilitate healing by providing a moist environment, controlling excessive exudate and bacterial contamination, and reducing pain.…”
Section: Discussionmentioning
confidence: 99%
“…treatments are used more frequently for pressure injuries of various stages. [38][39][40] However, these dressings are considered prophylactic rather than therapeutic. 41 Modern dressings facilitate healing by providing a moist environment, controlling excessive exudate and bacterial contamination, and reducing pain.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%